Implementasi Multi-Echelon Inventory Optimization (MEIO): Systematic Literature Review - Handik Agus Prasetyo; Yetty Dwi Lestari (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
Multi-Echelon Inventory Optimization (MEIO) refers to a strategic method for controlling inventory across multiple tiers of the supply chain, encompassing everything from suppliers to end retailers. Research related to MEIO remains fragmented, with diverse modeling techniques and limited empirical validation. This study presents a systematic literature review (SLR) on MEIO published during the period 2015–2025 using the PRISMA protocol. A total of 1,333 initial articles were identified from the Scopus, Crossref, and Google Scholar. The review results categorize MEIO research based on application domains, methodologies, optimization techniques, and performance indicators. Key findings reveal three research gaps: (1) limited integration of digital technologies such as blockchain and IoT, (2) a lack of empirical case studies in developing countries, and (3) the absence of a risk-based decision-making framework. The novelty of this study lies in providing a structured synthesis of MEIO research trends, proposing a conceptual framework for future applications, and delivering practical implications for academics and practitioners. This review contributes to the advancement of supply chain management by offering directions for innovation in multi-echelon inventory planning. Keywords: Multi-Echelon Inventory; Supply Chain Optimization; Systematic Literature Review; Risk Management; Digital Technology